THE ETHNIC COMPOSITION OF THE POPULATION OF REGION KASHKADARYA: CLASSIFICATION AND ANALYSIS - Iskandarov Sherzod Abduganievich (Web of Journals Publishing, 2025)
More attention focused on the country after gaining independence from our history. Etnogenez and ethnic history, including coverage on a number of scientific studies has conducted.